Effect of Fe(III)-bicarboxylic complexes in removal pollutant under UV and sunlight in aqueous solutions. Issue 17 (29th July 2022) - Seraghni, N.; Ghoul, I.; Dekkiche, B. A.; Bouaziz, C.; Debbache, N.; Sehili, T.
ABSTRACT: In this study, we have applied Fe(III)-bi-carboxylic acid solutions containing citrate and oxalate ligands to degrade 3-méthylphénol (3MP) in aqueous solutions both under UV and sunlight. Under irradiation at 365 nm, the photodegradation of 3MP is markedly better in the presence of the Fe(III)Ox complex than in the Fe(III)Cit complex this fact is explained by an excess of H2 O2 and Fe(II) generated by Fe(III)Ox photolysis creating the Fenton process. We mixtures were realized by varying the composition of the Fe(III)Cit and Fe(III)Ox in order to see the additives of the degradation efficiency of the pollutant. The results show that the addition of Fe(III)Ox to the Fe(III)Cit system evidently augmented the photodegradation rate at pH = 5.5. The Fe(III)Ox/Fe(III)Cit ratio is optimized at [Fe(III)Ox] (0.15/0.15)/[Fe(III)Cit] (0.15/0.6). Synergistic effect in the Fe(III)Ox/Fe(III)Cit binary system was confirmed. The addition of tertiobutanol (T-buOH) noticeably inhibited the photodegradation, indicating the involvement of OH in the process. To verify the feasibility of photochemical processes in the environment, tests on the photodegradation of 3MP were performed under natural irradiation. The degradation was improved under excitation by sunlight in the presence of Fe(III)-bi-carboxylic acid solutions containing citrate and oxalate ligands. These results are very encouraging for the application of this system for the treatment of organic pollutants in aqueous solution. GRAPHICAL ABSTRACT: UF0001